Using natural deep eutectic solvents for the extraction of metabolites in Byrsonima intermedia leaves. Issue 2 (30th November 2018) - Fraige, Karina; Arrua, R. Dario; Sutton, Adam T.; Funari, Cristiano Soleo; Cavalheiro, Alberto José; Hilder, Emily F.; Bolzani, Vanderlan da Silva
Abstract: Natural deep eutectic solvents have been used as an alternative to organic solvents for the extraction of plants metabolites, allowing for the extraction of compounds of different polarities, while being inexpensive, non‐toxic, and easy to prepare. This work presents the comparison of the chromatographic profiles by high‐performance liquid chromatography with diode‐array detection obtained from Byrsonima intermedia (Malpighiaceae) using five choline chloride‐based natural deep eutectic solvents, in addition to the most used traditional extraction solvents, methanol/water 7:3 and ethanol/water 7:3 v/v. A reference extract was used to tentatively identify compounds by high‐performance liquid chromatography with tandem mass spectrometry. The water content appeared to be important for the extraction efficiency and the mixture choline chloride/glycerol was shown to be the best candidate for efficiently extracting this matrix when compared with the traditional extraction media in addition to being far greener as shown by the environmental analysis tool. Seven phenolic compounds (digalloyl quinic acid, proanthocyanidin dimer, galloylproanthocyanidin dimer, quercetin‐ O ‐hexoside, galloyl quercetin hexoside, quercetin‐ O ‐pentoside, and galloyl quercetin pentoside) were tentatively identified in all extracts. Moreover, the influence of these solvents on the antioxidant activity of the extracts was studied and the results for choline chloride/glycerol extracts were very similar to that of the traditional extraction solvents.